Antibiotic use during coronavirus disease 2019 intensive care unit shape multidrug resistance bacteriuria: A Swedish longitudinal prospective study - Philip A. Karlsson; Philip A. Karlsson; Julia Pärssinen; Erik A. Danielsson; Nikos Fatsis-Kavalopoulos; Robert Frithiof; Michael Hultström; Michael Hultström; Miklos Lipcsey; Miklos Lipcsey; Josef D. Järhult; Helen Wang (Frontiers in Medicine, 2023)
ObjectivesHigh frequency of antimicrobial prescription and the nature of prolonged illness in COVID-19 increases risk for complicated bacteriuria and antibiotic resistance. We investigated risk factors for bacteriuria in the ICU and the correlation between antibiotic treatment and persistent bacteria.MethodsWe conducted a prospective longitudinal study with urine from indwelling catheters of 101 ICU patients from Uppsala University Hospital, Sweden. Samples were screened and isolates confirmed with MALDI-TOF and whole genome sequencing. Isolates were analyzed for AMR using broth microdilution. Clinical data were assessed for correlation with bacteriuria.ResultsLength of stay linearly correlated with bacteriuria (R2 = 0.99, p ≤ 0.0001). 90% of patients received antibiotics, primarily the beta-lactams (76%) cefotaxime, piperacillin-tazobactam, and meropenem. We found high prevalence of Enterococcus (42%) being associated with increased cefotaxime prescription. Antibiotic-susceptible E. coli were found to cause bacteriuria despite concurrent antibiotic treatment when found in co-culture with Enterococcus.ConclusionLonger stays in ICUs increase the risk for bacteriuria in a predictable manner. Likely, high use of cefotaxime drives Enterococcus prevalence, which in turn permit co-colonizing Gram-negative bacteria. Our results suggest biofilms in urinary catheters as a reservoir of pathogenic bacteria with the potential to develop and disseminate AMR.